2005
DOI: 10.1016/j.matbio.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis and comparative regional investigation of the extracellular matrix of the porcine temporomandibular joint disc

Abstract: Characterization of the extracellular matrix of the temporomandibular joint (TMJ) disc is crucial to advancing efforts in tissue engineering the disc. However, the current literature is incomplete and often contradictory in its attempts to describe the nature of the TMJ disc matrix. The aim of this study was to identify the variation of key matrix components along the three axes of the porcine disc using ELISAs to quantify these matrix components, immunohistochemistry to identify their regional distribution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 34 publications
4
125
0
Order By: Relevance
“…The advantage of this study's approach is that animal models could be compared with the human disc by the same testing methods in a consistent environment, mitigating variability associated with comparisons made across different studies. Because of the contradictory nature of results from prior studies, the results of this investigation do not agree with all prior work, but they are consistent with those of previous studies performed in our group using the pig model (Detamore and Athanasiou, 2003b;Athanasiou, 2005, 2006a;Detamore et al, 2005;Almarza et al, 2006). The interspecies characterization data collected here will provide valuable design parameters for tissue engineers seeking to recapitulate the properties of the disc in vitro, and for those looking to study functional replacements in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…The advantage of this study's approach is that animal models could be compared with the human disc by the same testing methods in a consistent environment, mitigating variability associated with comparisons made across different studies. Because of the contradictory nature of results from prior studies, the results of this investigation do not agree with all prior work, but they are consistent with those of previous studies performed in our group using the pig model (Detamore and Athanasiou, 2003b;Athanasiou, 2005, 2006a;Detamore et al, 2005;Almarza et al, 2006). The interspecies characterization data collected here will provide valuable design parameters for tissue engineers seeking to recapitulate the properties of the disc in vitro, and for those looking to study functional replacements in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…Detamore et al 24,25) reported that the articular disc was composed of fibroblast-and chondrocyte-like cells; however, they did not detect type II collagen expression. Similarly, we also did not observe type II collagen expression in the articular disc itself; however, type II collagen was intensely expressed around the lower joint space between 17.0 dpc and 3 dpn, during which time the lower joint space was formed.…”
Section: Discussionmentioning
confidence: 97%
“…The abundance of chondrocyte-like cells in the center of the TMJ disc compared with the periphery corresponds well to the elevated levels of chondroitin sulfate and higher compressive stiffness reported for the center of the disc. [20][21][22][23][24] Moreover, the higher relative number of chondrocyte-like cells on the inferior surface compared with the superior surface of the disc may shed light on functional differences between the inferior and superior joint spaces of the TMJ. These results may suggest a more mechanically demanding environment in the inferior joint space, which is supported by the observed increased levels of degeneration in the inferior space in cases of TMJ disorders.…”
Section: Discussionmentioning
confidence: 99%